Practice Patterns of Referring Physicians in Management of the Dysphonic Patient. (20th February 2018) - Holcomb, Andrew J.; Hamill, Chelsea S.; Irwin, Thomas; Sykes, Kevin; Garnett, James D.; Kraft, Shannon
Abstract : Objective: Dysphonia is commonly encountered by primary care physicians and general otolaryngologists. We examine practice patterns of referring physicians to a tertiary voice clinic, including adherence to evidence‐based guidelines. Study Design: Retrospective case series with chart review. Setting: Academic tertiary care hospital. Subjects and Methods: In total, 821 charts of patients with voice complaints seen at a tertiary voice clinic between January 2011 and June 2016 were reviewed. Included charts (n = 755) were reviewed for type of referring provider, prior diagnoses, and treatments employed by referring physicians. Additional information regarding findings at the time of laryngoscopy/stroboscopy and diagnoses provided by a laryngologist were also obtained. Statistical analysis was performed to determine significant relationships between variables of interest. Results: A total of 244 patients (32.2%) received a diagnosis prior to evaluation in the voice clinic, most commonly laryngopharyngeal reflux disease (n = 134). Prior medical treatment was attempted in 221 (29.3%) patients, typically antireflux medications (n = 141). Of the patients treated with proton pump inhibitors by referring physicians, 65.1% lacked symptoms of gastroesophageal reflux disease. Patients with prior treatment had a median duration of symptoms 6 weeks longer than those without prior treatment ( P =. 04). Among previously diagnosed patients, 199 (81.6%) of diagnoses changed after evaluation in the voice clinic. Conclusion: Referring physicians frequently treat dysphonic patients empirically, often with antireflux medications. Subspecialist evaluation results in changes in diagnosis in many patients. Empiric treatment can delay referral and appropriate treatment.